2018
DOI: 10.1080/01658107.2018.1488175
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Angiography of Macula in Chronic Anterior Ischaemic Optic Neuropathy Associated with Giant Cell Arteritis

Abstract: A 74-year-old man presented with bilateral optic nerve atrophy related to arteritic anterior ischaemic optic neuropathy (AION) which started 22 years ago. Atrophic papilla was noted in both eyes and optical coherence tomography showed thinning of the retinal nerve fibres layer as well as the macular ganglion cell complex. Optical coherence tomography angiography of the macula found a decreased density of the superficial capillary complex, whereas deep capillary complex was well-preserved. Inner retinal layer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…Gaier et al reported superficial capillary dilation in the peripapillary region in patients with acute AAION 142 . Other OCT angiography (OCTA) findings in GCA include superficial and deep retinal capillary non‐perfusion, superficial capillary dilation overlying areas of choroidal ischemia, reduced choroidal perfusion and reduced signal from all lamina corresponding to cotton wool spots and disc swelling 142‐145 …”
Section: Investigationsmentioning
confidence: 99%
“…Gaier et al reported superficial capillary dilation in the peripapillary region in patients with acute AAION 142 . Other OCT angiography (OCTA) findings in GCA include superficial and deep retinal capillary non‐perfusion, superficial capillary dilation overlying areas of choroidal ischemia, reduced choroidal perfusion and reduced signal from all lamina corresponding to cotton wool spots and disc swelling 142‐145 …”
Section: Investigationsmentioning
confidence: 99%
“…Several groups reported OCT-A measurements of optic nerve head perfusion of AAION or NAION patients in the acute or non-acute state [ 32 , 33 , 34 , 35 , 36 , 37 ]. In summary, non-acute NAION shows significantly increased optic disc non-perfusion areas that correlate well with visual field defects and best corrected visual acuity (BCVA) [ 32 , 34 ].…”
Section: Oct-a Findings In Neurological Diseasesmentioning
confidence: 99%
“…Similarly, the group of Pierro et al described vessel density and vessel tortuosity changes in acute AAION and NAION cases that correlated well with RNFL reduction and visual field defects [ 36 ]. A case report study of a chronic AAION explicitly measured OCT-A of the macular region and found that only the superficial capillary plexus was decreased, whereas deep capillary plexus and choriocapillaris were normal [ 35 ].…”
Section: Oct-a Findings In Neurological Diseasesmentioning
confidence: 99%
“…In addition, a strong correlation of vascular measurements and the RNFL and visual field defects has been found [23]. In the case report of Mahdjoubi et al [24], where the macular region of a patient with remote (22 years earlier) AAION was evaluated on OCTA, it was noted that vessel density was reduced in the SCP and not in the deep capillary plexus and choriocapillaris layers and that the fovea avascular zone was well preserved. Vessel density decrease in the peripapillary region of chronic AAION as well as of the fellow unaffected eye was observed in an 85-year-old male patient in the study of Chen et al [25].…”
Section: Introductionmentioning
confidence: 95%